Analysis of treatment results 389 patients with congenital blepharoptosis - Kobus, Kazimierz; Wójcicki, Piotr; Rychlik, Dariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: Retrospective analysis of the results in the treatment of congenital blepharoptosis. Material and methods: We retrospectively reviewed the records of 389 patients with blepharoptosis who underwent surgical treatment in the Hospital of Plastic Surgery in Polanica-Zdrój, from January 1976 to January 2005. The age of patients, degree of malformation and unilateral or bilateral occurrence of ptosis, was analyzed. Moreover, we studied treatment results of patients with blepharoptosis treated in our hospital and patients treated elsewhere, before admission to our hospital. Results: 218 patients from 327 operated in our hospital had levator muscle resections. After 6 months of observation 39 patients were qualified for surgical re-correction. 12 months after surgery 4 patients had recurrence of ptosis . Frontalis suspension technique with using the temporal fascia,was performed in 109 patients. After 6 months observation, 8 patients were qualified for surgical re-correction. Conclusions: For patients with maintained function of the levator muscle the most effective and physiological procedure, is the muscle shortening. Frontalis suspension technique with use of the temporal fascia should be limited to treat failure cases and patients with poor or absent function of the levator muscle.